Influence of Ion Generation–Recombination on Dielectric Relaxation Time in Electrolytes - Ioannis Lelidis; Giovanni Barbero (Liquids, 2025)
The well-known Poisson–Nernst–Planck model is a classical approach usedto describe ion transport in liquids. Extended versions of this model account for thegeneration–recombination of ions at equilibrium. In this paper, we investigate the influenceof the generation–recombination term on dielectric relaxation in an electrolytic cell shapedlike a slab, bounded by two parallel blocking electrodes. We show that in the adiabaticlimit—which holds when the reaction time is much longer than the dielectric relaxationtime—the electric current in the external circuit does not follow a simple relaxation mechanism.Instead, it is characterized by two distinct relaxation times: a short relaxationtime associated with dielectric relaxation and a longer relaxation time related to the iondissociation–association process. Conversely, this information could be used to assess thepresence and/or significance of the generation–recombination effect in an electrolytic cell.